Printable wax-based sacrificial template and metal-based composite material constructed by using same

By using printable wax-based sacrificial template compositions and a two-stage demolding process, the contradiction between molding accuracy and material selection and demolding method in existing technologies has been resolved, achieving stable molding and non-destructive demolding of high-precision complex structures, and improving the comprehensive mechanical properties of metal-ceramic composite materials.

CN120988495APending Publication Date: 2025-11-21JILIN UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511151597.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-18
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

Existing technologies for preparing metal-ceramic composite materials suffer from contradictions between molding precision and material selection, between demolding methods and structural complexity, and insufficient template material properties. These issues result in low molding precision, low demolding efficiency, and poor material bonding, making it difficult to achieve high-quality composite material preparation.

Method used

A printable wax-based sacrificial template composition, including a paraffin matrix, microcrystalline wax, polymer modifier, and composite organic acid additive, is used to form a high-precision, complex-structured metal matrix composite material through direct ink writing 3D printing technology. This is combined with a two-stage demolding process of solvent extraction and low-temperature pyrolysis.

Benefits of technology

It achieves stable molding and non-destructive demolding of high-precision complex structures, ensuring the integrity of the ceramic skeleton and the uniform infiltration of liquid metal, and improving the comprehensive mechanical properties of the composite material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120988495A_ABST
    Figure CN120988495A_ABST
Patent Text Reader

Abstract

The invention is suitable for the technical field of additive manufacturing, and provides a printable wax-based sacrificial template and a metal-based composite material constructed by using the printable wax-based sacrificial template, the template comprises a paraffin matrix, microcrystalline wax, polyethylene wax, an ethylene-vinyl acetate copolymer and a composite organic acid auxiliary agent composed of stearic acid and palmitic acid according to a specific ratio, the formula is precisely designed to achieve excellent direct ink writing (DIW) printing performance, and a novel'solvent extraction-low temperature pyrolysis' two-stage synergistic demolding process is adapted. Through collaborative design of a material formula, a printing process and a demolding strategy, the technical contradiction between stable forming and lossless demolding of a high-precision sacrifice template with a complex structure is overcome, and the high-performance metal-ceramic composite material can be manufactured.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the field of additive manufacturing technology, and particularly relates to a printable wax-based sacrificial template and a metal matrix composite material constructed using the same. BACKGROUND

[0002] Metal-ceramic composites have great application potential in the fields of aerospace, automobiles and electronic packaging due to their excellent specific strength, specific stiffness and high-temperature resistance. The key technology for preparing composite materials with complex internal structures (such as biomimetic structures, network interpenetrating structures) is the sacrificial template method combined with liquid metal infiltration. However, the success of this technology path is highly dependent on the forming precision, structural stability of the sacrificial template and the non-destructive nature of the demolding process.

[0003] In the prior art, sacrificial templates based on light-cured 3D printing technology (such as DLP) are often used to prepare resin-based or inorganic salt / resin composite-based sacrificial templates. For example, patent application No. 202411640145.8 discloses a method of using DLP to print a calcium carbonate / resin mold, pouring ceramic slurry into the mold, and finally removing the sacrificial phase by using strong acid (hydrochloric acid) corrosion after high-temperature sintering and converting calcium carbonate into calcium oxide. This method is feasible, but the demolding process requires high-temperature pyrolysis and strong acid corrosion, which is a drastic treatment method that can easily cause micro-cracks or even macro-cracks in the ceramic green body, especially for thin-walled or delicate structures, resulting in a low yield. Moreover, for ceramic materials that cannot be sintered in air (easily oxidized), this demolding method can also cause pore blockage and infiltration defects. In addition, there may be an interface reaction between CaO and the ceramic material during high-temperature sintering, which can change the interface bonding between the ceramic and the infiltrated metal.

[0004] In order to overcome the drawbacks of high-temperature demolding, researchers have begun to explore the use of low-temperature soluble sacrificial templates. The core idea of this route is to use additive manufacturing technology to prepare a polymer template that can be dissolved in a specific solvent, thereby achieving demolding under mild conditions. For example, the existing technology Ceramics International 46 (2020) 25220-25229 reports in detail a process for printing an ABS+ plastic mold using FDM technology and preparing a zirconia ceramic part by combining gel casting. In this process, demolding is achieved by soaking the green body in acetone and assisted by manual removal. This study proves the feasibility of using soluble templates to indirectly form high-density ceramic parts.

[0005] However, analyzing this type of technology route represented by the above content, it can be found that it still has several fundamental limitations and unsolved technical problems. These fundamental limitations reveal a long-standing technical contradiction in this field:

[0006] The contradiction between the forming precision and the material selection:

[0007] The inherent precision limit of the forming technology and the limitation of the material selection: the FDM technology adopted in the above technical solution is essentially the layer-by-layer stacking of the melted filament, and the resolution is usually in the range of 100-400 microns, which is difficult to manufacture internal network structures with sub-hundred-micron fine features or complex curved surfaces. More importantly, FDM technology strongly depends on pre-made high polymer filaments, which limits the innovation of the material system from the source. Users can only passively choose several commercially available soluble filaments (such as ABS, PVA), and cannot actively and systematically design and optimize the formula according to the multiple properties (rheological property, thermal stability, shrinkage, interlayer bonding force) required by the sacrificial template. This leads to the problems of weak interlayer bonding force, obvious anisotropy, and easy warping deformation of the printed template;

[0008] The contradiction between the demolding method and the structural complexity: the demolding process is heavily dependent on "long soaking + manual removal". This "long soaking + manual removal" method is not only inefficient and labor-intensive, but more critically, it is only suitable for ceramic pieces with simple shape and open structure (such as the vase and gear shown in the disclosure), because the operator needs enough space to physically peel off and scrape off the softened ABS+residue. For composite preforms with complex three-dimensional interpenetrating networks or fine closed channels, this manual intervention is completely infeasible. In addition, long-term acetone soaking (more than 48 hours to completely dissolve, as mentioned in the document) can cause the solvent to penetrate into the interior of the ceramic body, which can easily cause swelling or micro-cracks, seriously damaging the integrity of the body;

[0009] The fundamental deficiency of the template material performance: the single-component thermoplastic plastic (ABS+) used in the above technical solution is soluble, but it is not optimized for the harsh working conditions of the sacrificial template. Pure thermoplastic plastics generally have the problems of large solidification shrinkage and poor thermal stability. During the contact and co-solidification with ceramic slurry (especially water-based slurry), the changes in temperature and humidity will cause the size change and creep of the template, resulting in the decrease of the precision and the structural deformation of the final ceramic framework.

[0010] In summary, although the concept of soluble sacrificial template has been proposed, the existing technology (whether based on light-cured resin template or FDM-printed ABS template) has obvious shortcomings in the three core links of the comprehensive performance of the template material, the precision and freedom of the forming technology, and the non-destructiveness and universality of the demolding process; as a low-melting-point material, paraffin can be removed by mild heating or solvent dissolution, and in theory it can also be used as a sacrificial template; however, when paraffin is applied to high-precision additive manufacturing (especially direct ink writing, DIW), it faces new challenges: pure paraffin has low mechanical strength, poor thermal stability, and large solidification shrinkage, and problems such as structure collapse, layer separation and poor size accuracy often occur during printing. Simply blending paraffin with other polymers is also difficult to systematically solve the comprehensive performance balance of its melting fluidity, solidification shrinkage, forming strength and interlayer bonding force.

[0011] Therefore, there is an urgent need for a completely new and systematic technical solution that must synergistically optimize the material design of the sacrificial template, the high-precision forming technology, and the non-destructive demolding process as an indivisible whole, so as to realize the whole-process collaborative control from template design, accurate forming to non-defective demolding, and high-quality infiltration. SUMMARY

[0012] The purpose of the embodiment of the present application is to provide a printable wax-based sacrificial template and a metal matrix composite material constructed by using the same, aiming to solve the technical contradictions proposed in the background art.

[0013] The embodiment of the present application is implemented as follows: the printable wax-based sacrificial template composition comprises the following raw materials in mass percentage: paraffin matrix: 60-70%, microcrystalline wax: 5-10%, polymer modifier: 27-35%, and composite organic acid additive: 1-3%; wherein the polymer modifier is composed of polyethylene wax and ethylene-vinyl acetate copolymer, and the mass ratio of the two is 1:(2.5-3.5); the composite organic acid additive is composed of stearic acid and palmitic acid, and the mass ratio of the two is 1:(1-1.5).

[0014] Another purpose of the embodiment of the present application is to provide a preparation method of a metal matrix composite material constructed by using the printable wax-based sacrificial template, comprising the following steps:

[0015] (a) providing the printable wax-based sacrificial template as a printing ink;

[0016] (b) using a direct ink writing 3D printing technology to extrude the printing ink in a heated state into a sacrificial template with a preset three-dimensional network structure;

[0017] (c) impregnating the sacrificial template into a ceramic slurry and solidifying the slurry to form a ceramic-template composite green body;

[0018] (d) performing a two-stage collaborative debinding process on the composite green body to remove the sacrificial template without damage, obtaining a porous ceramic preform with high structural integrity, specifically comprising:

[0019] (d1) solvent extraction stage: placing the composite green body in an organic solvent to preferentially dissolve and remove most of the low molecular weight components in the sacrificial template, forming a through-pore network inside the green body to pre-release internal stress during subsequent heat treatment;

[0020] (d2) low-temperature pyrolysis stage: performing a programmed temperature heat treatment on the green body treated in step (d1) to make the remaining high molecular weight components of the sacrificial template gasify and decompose completely;

[0021] (e) high-temperature sintering of the porous ceramic preform;

[0022] (f) filling the pores of the sintered porous ceramic preform with molten metal or its alloy by pressure infiltration, and obtaining the metal matrix composite after cooling.

[0023] Another object of the embodiments of the present application is to provide a metal matrix composite prepared by the above method, which comprises a three-dimensionally continuous and topologically designed metal matrix phase, and a ceramic reinforcing phase filled in the metal phase network.

[0024] The embodiments of the present application have the following beneficial effects:

[0025] 1. The unification of stable forming and lossless debinding of high-precision complex structures is achieved: the multi-component collaborative wax-based system provided by the embodiments of the present application solves the contradiction between traditional wax-based materials "removable but not printable" and traditional resin materials "printable but difficult to remove" through the clear functional division of each component, and fundamentally avoids the cracking of ceramic green bodies due to severe thermal stress or chemical corrosion during the debinding process through the innovative "solvent extraction-low temperature pyrolysis" collaborative debinding process;

[0026] 2. A manufacturing strategy with full-process collaborative control is established: the embodiments of the present application establish a systematic process from dynamic matching of material rheological properties, DIW printing parameters (such as temperature, pressure, speed), to two-stage debinding process control, which ensures the stable connection of each link and is a reliable guarantee for realizing the high performance of the final composite material;

[0027] 3. The performance and reliability of the final composite material are improved: since the demolding process is gentle, thorough and non-destructive, the obtained ceramic skeleton channel is clean and structurally complete, which is conducive to the complete and uniform infiltration of liquid metal, which ensures the internal density of the composite material and forms a high-quality metal-ceramic interface, thereby making it exhibit excellent comprehensive mechanical properties. BRIEF DESCRIPTION OF DRAWINGS

[0028] Figure 1 A metal matrix composite material preparation flowchart using a printable wax-based sacrificial template composition is provided for the embodiments of the present application;

[0029] Figure 2 In a, a wax-shaped sacrificial mold printing process diagram is provided for Embodiment 1 of the present application, b is an inner concave honeycomb structure paraffin template, and c is a sawtooth structure paraffin template;

[0030] Figure 3 In a, a honeycomb structure ceramic preform is provided for Embodiment 2 of the present application, b is a micro-SEM image thereof; c is an Al / SiC composite material after metal infiltration, d is a microstructure image thereof, and the inserted drawing is a local enlarged view;

[0031] Figure 4 An energy spectrum (EDS) analysis diagram of the interface region of the Al / SiC composite material provided for Embodiment 2 of the present application is provided;

[0032] Figure 5 The bending stress-strain curve diagram of the Al / SiC composite material corresponding to the honeycomb wax-shaped sacrificial mold prepared by different printing needle specifications (23G, 25G, 27G) in three orientations (a: XOY, b: YOZ, c: XOZ) is provided for Embodiment 2 of the present application. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical scheme and advantages of the present application more clear and explicit, the present application will be further described in detail below in combination with the drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and do not limit the present application.

[0034] The printable wax-based sacrificial template composition comprises the following raw materials by mass percentage:

[0035] The paraffin matrix 60-70% as the main body and low-temperature removable phase of the composition, preferably, the paraffin matrix is full refined paraffin to provide basic rigidity and formability;

[0036] The microcrystalline wax 5-10% as a dimensional stabilizer, the irregularity of its molecular structure effectively inhibits the crystallization and phase change shrinkage of paraffin during the cooling and solidification process, significantly improving the dimensional accuracy and thermal deformation resistance of the template;

[0037] Polymer modifier: 27-35%, consisting of polyethylene wax and ethylene-vinyl acetate copolymer, with a mass ratio of 1:(2.5-3.5), wherein the polyethylene wax acts as a rheological modifier and mechanical reinforcing agent, which can increase the viscosity of the system in the molten state, prevent the collapse of printed lines, and form a reinforcing network after solidification, thereby improving the overall strength and toughness of the template, making it sufficient to support its own weight and the stress during subsequent processing, preferably, the melting point thereof is 90-110°C, and the molecular weight thereof is 5000-12000 g / mol;

[0038] Ethylene-vinyl acetate copolymer as an interlayer adhesion regulator and toughener, the polar groups thereof improve the wettability and adhesion between printed layers, prevent delamination, and the flexible segments thereof further improve the toughness of the template, preferably, the content of vinyl acetate therein is 18-28%;

[0039] Complex organic acid additive: 1-3%, consisting of stearic acid and palmitic acid, with a mass ratio of 1:(1-1.5), the binary additive system thereof acts synergistically, wherein the longer-chain stearic acid (C18) mainly provides efficient external lubrication on the inner wall of the nozzle during melt extrusion, thereby reducing the extrusion resistance; and the shorter-chain palmitic acid (C16) improves the compatibility and flowability of the components in the composition, thereby achieving the dual effects of internal lubrication and plasticization, which together ensure the high homogeneity, stability, and smooth extrusion of the printing ink.

[0040] The above-described printable wax-based sacrificial template composition is designed to have the following synergistic properties to adapt to high-fidelity printing and subsequent low-stress demolding processes:

[0041] (a) Printing rheology: the apparent viscosity is 3-30 Pa·s in the range of 1-100 s -1 of shear rate at 85-115°C, and exhibits shear thinning characteristics;

[0042] (b) Structural self-supporting property: the storage modulus G' of the solidified entity after printing thereof is not less than 5x10 4 Pa at room temperature;

[0043] (c) Programmable removability: the components thereof are suitable for removal by a two-stage synergistic process combining solvent extraction and low-temperature pyrolysis.

[0044] A metal matrix composite material constructed using a printable wax-based sacrificial template, the preparation method thereof comprising the following steps:

[0045] (1) Sacrificial template additive manufacturing: Direct ink writing (DIW) 3D printing technology is adopted, a printable wax-based sacrificial template composition is heated and melted to form a printable ink, and is extruded layer by layer according to a three-dimensional model file to form a sacrificial template with a preset three-dimensional network structure, which realizes accurate reproduction of complex geometric configurations (such as honeycomb, recessed honeycomb, topologically optimized structure, etc.);

[0046] (2) Preparation of ceramic-template composite green body: ceramic powder (such as SiC), solvent (deionized water and gel resin), sintering aid and various additives (such as composite dispersant, including tetramethylammonium hydroxide and polyethylene glycol, the former stabilizes the slurry through electrostatic repulsion, and the latter prevents particle agglomeration through steric hindrance, and an initiator can also be included) are mixed to prepare a ceramic slurry with high solid content and low viscosity, the sacrificial template prepared in step (1) is immersed in the slurry, and the gel resin is solidified by mild heating to form a ceramic-template composite green body that completely covers the sacrificial template;

[0047] (3) Staged and coordinated demolding: used for losslessly removing the sacrificial template to obtain a complete ceramic preform, which comprises:

[0048] (3a) Solvent removal stage: the composite green body is soaked in an organic solvent (such as gasoline, kerosene, petroleum ether) and treated at a mild temperature (such as 40-60°C), which uses the high solubility of the paraffin matrix in the solvent to remove most of the sacrificial template, thereby forming an initial interconnected pore network in the green body and effectively releasing the internal stress caused by material shrinkage mismatch;

[0049] (3b) Pyrolysis removal stage: the solvent-treated green body is subjected to multi-stage and programmed temperature rising heat treatment, for example, first slowly heated to below 220°C to gently remove residual paraffin and low molecular weight components in a gasification manner; then slowly heated to about 450°C to completely remove polyethylene wax, EVA and other high molecular weight enhancers, modifiers and gel resins in a thermal decomposition manner, this coordinated process avoids the severe stress of single high temperature pyrolysis and ensures the structural integrity of the ceramic preform;

[0050] (4) Sintering and metal infiltration: the demolded and clean porous ceramic preform is sintered at high temperature to enhance its mechanical strength, and then a pressure infiltration technique is used to force molten metal (such as aluminum or aluminum alloy) to fill all the pores of the ceramic preform under the action of high pressure gas, and after cooling, a dense metal matrix composite material with an internal "metal phase continuous, ceramic phase isolated (or interpenetrating)" network structure is obtained.

[0051] The specific implementation of the present application is described in detail below with specific examples.

[0052] Example 1, printable wax-based sacrificial template, which is prepared into a printable sacrificial template ink, comprising the following steps:

[0053] Composition preparation: 60% of full refined paraffin wax (melting point 62℃), 10% of microcrystalline wax, 7% of polyethylene wax (melting point 105℃, molecular weight ~8000g / mol), 21% of ethylene-vinyl acetate copolymer (EVA, VA content 18%), 0.8% of stearic acid and 1.2% of palmitic acid are weighed according to mass percentage;

[0054] All components are placed in a heating jacket with magnetic stirring function, heated at 115℃ and stirred at a rate of 300rpm for 3h, until all components are completely melted and form a uniform transparent mixed melt, which is a printable ink.

[0055] Printability verification: the printable ink prepared in Example 1 is transferred to the heated cartridge of the DIW 3D printer, and kept at 120℃ for 30min. A 27G (inner diameter 210μm) stainless steel nozzle is selected, and printing is carried out on a constant temperature forming platform at 50℃ according to the preset inner recess honeycomb model (as shown in Figure 2 b, with a honeycomb side length of 1.5mm) (or other cross grid, spiral, fractal topology, topology optimization configuration, etc. as shown in Figure 2 c) can also be used); the printing parameters are set as follows: extrusion air pressure 5atm, printing speed 10mm / s, layer height 0.18mm; during printing, the ink extrudes smoothly, the lines are uniform, solidification is rapid, and the interlayer bonding is good. After printing, the inner recess honeycomb structure sacrificial template as shown in Figure 2 b is obtained, which is structurally complete without collapse, fracture or obvious deformation, proving that the composition has excellent DIW forming performance.

[0056] Example 2, honeycomb structure Al / SiC composite material based on sacrificial template, the process is as shown in Figure 1 , which specifically comprises the following steps:

[0057] (1) Sacrificial template preparation: a three-dimensional modeling software (Solidworks) is used to design a honeycomb structure model (side length 1.5mm) and a material collection channel: the top side wall of the model is extended by 3mm along the printing direction to accommodate the excess slurry during subsequent pouring, ensuring the structural integrity of the ceramic column and the top connecting plate; the model is converted into a G-code printing file, and the printable ink prepared in Example 1 is used to print the sacrificial template by DIW technology, with the following printing parameters: cartridge temperature 120℃, nozzle specification 25G, inner diameter 260μm (or 23G, 27G can also be selected), forming platform temperature 50℃, air pressure 3.5atm, printing speed 10mm / s, layer height 0.23mm;

[0058] (2) Ceramic slurry preparation and green body preparation: A high solid content ceramic slurry was prepared with the following composition: 50 vol% SiC powder (a mixture of 10 μm and 1 μm SiC powders in a mass ratio of 4:1 to form an optimized particle size distribution), 50 vol% solvent (a mixture of deionized water and gel resin, in which the gel resin was prepared by mixing DMAA and MBAM in a volume ratio of 10:1), 1 wt% of the total mass of SiC powder of a composite dispersant (TMAH and PEG6000 in a mass ratio of 1:4), and 15 wt% of the total mass of SiC powder of a sintering aid (Al2O3 and MgO in a mass ratio of 7:1); all components were mixed in a planetary ball mill at a speed of 200 rpm for 10 h to obtain a uniform, low viscosity ceramic slurry. The slurry was vacuum degassed to remove air bubbles, then 0.1 wt% of the total mass of gel resin of ammonium persulfate (APS) was added as an initiator and dispersed uniformly by magnetic stirring, and then poured into a pre-prepared mold; the honeycomb wax template prepared in step (1) was slowly pressed into the slurry until it was completely immersed, and the entire mold was placed on a 40°C water bath heating platform for 30 min to allow the gel resin to solidify. After solidification, the ceramic-template composite green body was removed from the mold;

[0059] (3) Multi-stage coordinated demolding to obtain a porous ceramic framework:

[0060] First, the solvent removal stage: the composite green body was completely immersed in 92# gasoline and treated in a 50°C water bath for 1 h. This step was designed to dissolve most of the paraffin matrix, form a connected pore network, and effectively release the initial stress caused by the mismatch of the thermal expansion coefficients of the materials.

[0061] Then, the pyrolysis removal stage: the solvent-treated green body was dried in a vacuum drying oven at 80 Pa and 60°C for 1 h to remove residual solvents. Then, the dried green body was placed in a box furnace and subjected to programmed temperature pyrolysis in an air environment: heated to 200°C at a rate of 1°C / min and held for 30 min; then heated to 450°C at a rate of 0.5°C / min and held for 1 h. This stage was designed to gently and completely remove residual polyethylene wax, EVA, and other high molecular components.

[0062] (4) Sintering and pressure infiltration: continue to sinter the demolded ceramic preform (i.e. porous ceramic skeleton) in a box furnace: heat up to 650℃ at a rate of 2℃ / min, then heat up to 1200℃ at a rate of 5℃ / min, keep for 2h, then cool down at a rate of 5℃ / min, to obtain a porous SiC ceramic skeleton with sufficient strength; put the sintered SiC ceramic skeleton and pure aluminum ingot (mass sufficient to fill all pores) into an alumina crucible, with the aluminum ingot above the skeleton, move the crucible into a pressure infiltration furnace, vacuumize to below 10 Pa, heat up to 800℃ at a rate of 5℃ / min and keep for 10 min, so that the aluminum ingot completely melts, then introduce high-purity argon into the furnace to 3 MPa and keep for 5 min, forcing the liquid aluminum to completely infiltrate into the micro-pores of the ceramic skeleton, finally cool down to room temperature at a rate of 5℃ / min, take out the sample, to obtain the final Al / SiC composite material.

[0063] Analyze the porous SiC ceramic skeleton and Al / SiC composite material prepared in Example 2, and obtain the results as shown in Figure 3 Fig. a-b and c-d, according to a-b, the skeleton structure is complete, and the fine features of the sacrificial template are reproduced, and sintering necks are formed between the particles, and the pores are unobstructed; according to c-d, the Al-based metal phase (brighter area in the figure) is continuously distributed, and the SiC reinforcing phase (darker area in the figure) is distributed in the form of isolated honeycomb columns, and the interface between the two is tightly combined, without obvious pores or cracks;

[0064] Analyze the elemental composition of the Al / SiC composite material, and obtain the EDS spectrum as shown in Figure 4 The analysis confirms the distribution and purity of the Al and SiC phases;

[0065] Test the bending strength of the Al / SiC composite material, and obtain the results as shown in Figure 5 It can be seen that the composite material exhibits excellent strength and toughness.

[0066] Example 3: Preparation of circular column array structure Al / SiC composite material based on sacrificial template, specifically including the following steps:

[0067] Similar steps as in Example 2 are adopted, with the following differences:

[0068] (1) The sacrificial template model is designed as a circular column array (cylinder diameter 2 mm, column spacing 2 mm);

[0069] (2) When DIW printing, a 27G nozzle is selected, the layer height is set to 0.18 mm, and the air pressure is adjusted to 5 atm, to match the finer structural features;

[0070] (3) The SiC solid content in the ceramic slurry is adjusted to 40 vol% to obtain better fluidity, ensuring that the slurry can completely fill the small inter-column voids;

[0071] Finally, high-quality and structurally complete circular column reinforced Al / SiC composite materials are also obtained, proving that the preparation method proposed in the embodiments of the present application has good universality and scalability and can be used to prepare various metal matrix composite materials of complex configurations.

[0072] The above merely describes preferred embodiments of the present application and is not intended to limit the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A printable wax-based sacrificial template, characterized in that, The raw materials include the following mass percentages: Paraffin base: 60-70%; microcrystalline wax: 5-10%; polymer modifier: 27-35%; composite organic acid additive: 1-3%.

2. The printable wax-based sacrificial formwork according to claim 1, wherein, The polymer modifier is composed of polyethylene wax and ethylene-vinyl acetate copolymer, and the mass ratio of polyethylene wax to ethylene-vinyl acetate copolymer is 1:(2.5-3.5), wherein the weight average molecular weight of the polyethylene wax is 5000-12000 g / mol, and the melting point is 90-110℃, and the mass content of vinyl acetate in the ethylene-vinyl acetate copolymer is 18-28%.

3. The printable wax-based sacrificial formwork according to claim 1, wherein, The composite organic acid additive is composed of stearic acid and palmitic acid, and the mass ratio of stearic acid to palmitic acid is 1:(1-1.5).

4. A method for producing a metal matrix composite material using the printable wax-based sacrificial template according to claim 1, characterized by, The method comprises the following steps: (a) providing the printable wax-based sacrificial template as a printing ink; (b) using a direct ink writing 3D printing technology to extrude the printing ink into a sacrificial template with a preset three-dimensional network structure in a heated state; (c) immersing the sacrificial template in a ceramic slurry and allowing the slurry to solidify to form a ceramic-template composite green body; (d) performing a two-stage coordinated demolding process on the composite green body to remove the sacrificial template without damage and obtain a porous ceramic preform with high structural integrity, specifically including: (d1) solvent extraction stage: placing the composite green body in an organic solvent to preferentially dissolve and remove most of the low molecular weight components in the sacrificial template, forming a through-pore network inside the green body to pre-release internal stress during subsequent heat treatment; (d2) low-temperature pyrolysis stage: subjecting the green body treated in step (d1) to programmed temperature heat treatment to make the remaining high molecular weight components of the sacrificial template gasify and decompose and be completely removed; (e) high-temperature sintering of the porous ceramic preform; (f) filling a molten metal or its alloy into the pores of the sintered porous ceramic preform by pressure infiltration, and obtaining the metal matrix composite after cooling.

5. The method of claim 4, wherein, The printing process parameters in step (b) include: the temperature of the printing nozzle is 100-130℃, the temperature of the forming platform is 45-55℃, the extrusion gas pressure is 2-5atm, and the printing speed is 5-15mm / s.

6. The method of claim 4, wherein, The three-dimensional network structure in step (b) is a topological configuration with periodic or non-periodic characteristics, selected from at least one of honeycomb, concave honeycomb, cross grid, spiral, fractal, and topologically optimized configuration.

7. The method of claim 4, wherein, The ceramic slurry in step (c) contains: 20-60vol% SiC powder, sintering aid, and a gel resin system containing N,N-dimethylacrylamide and N,N'-methylenebisacrylamide; wherein the SiC powder is composed of at least two different particle sizes with a particle size range of 0.5-125μm.

8. The method of claim 4, wherein, The specific parameters of step (d1) are: the solvent extraction stage is treated with gasoline, kerosene or petroleum ether at a temperature of 40-60℃ for 1-2 hours. The specific parameters of step (d2) are: the low-temperature pyrolysis stage is heating to 180-220℃ at a rate of 0.5-2℃ / min and holding, and then heating to 400-450℃ at a rate of 0.5-3℃ / min and holding.

9. A metal matrix composite material, characterized by, The composite material is prepared by the method as claimed in any one of claims 4-8, and comprises a three-dimensionally continuous and topologically designed metal matrix phase, and a ceramic reinforcing phase filled in the metal phase network.

Citation Information

Patent Citations

  • Al / SiC composite material with continuously distributed metals and preparation method of Al / SiC composite material

    CN119433325A